Forage selection overlap between co-occurring introduced ungulates: insights for conservation management of a Sub-Antarctic Island - Salom, Amira (2025)
The presence of exotic herbivores can have detrimental effects on insular ecosystems because it usually involves the introduction of a previously absent functional group. Understanding feeding behavior is crucial to manage potential impacts, as it provides valuable information on which species may be most susceptible to the actions of these herbivores. We estimated diet selection of introduced red deer (Cervus elaphus) and goats (Capra hircus) in western Isla de los Estados, Argentina. We conducted floristic surveys to assess plant composition and forage availability at the landscape level. We evaluated the diet of both ungulates through microhistological analysis of feces during two spring-summer seasons. Overall, we detected 44 plant taxa in their feces, representing 67.7% of the plant richness detected in the field. Diet composition was similar between species, including a wide range of vascular plants and two groups of non-vascular plants, though both were dominated by a few species of shrubs and forbs. Nonetheless, both species select grasses, predominantly found in marine tussock grasslands, and trees mainly found as seedlings and sapling in forests and stunted trees in wetlands. Our results suggest that the introduced species exhibit overlapping forage selection, possibly having negative synergic effects on forest and grassland regeneration. This is concerning as these grasslands are of great importance for seabirds’ reproduction. Our findings provide valuable information to develop management plans for the conservation of this unique island ecosystem.